Evaluating the effect of VersaWrap tendon protector on functional outcomes in operative tendon repairs - Adu, Yaw; Harder, Justin; Cox, Cameron; Baum, Gracie; Hernandez, Evan J.; MacKay, Brendan J. (Frontiers in Surgery, 2024)
BackgroundTendon repairs often result in adhesion formation which can cause persisting functional deficits. Close proximity of healing tissues increases friction during tendon excursion, often leading to tendon tethering postoperatively. Despite continued improvements in techniques for tendon repairs, there is currently no consensus on the most effective modality to reduce adhesion formation. The VersaWrap Tendon Protector is a bioresorbable hydrogel that is FDA-cleared for use in tendon repair by separating healing tendons from surrounding tissues and improving tendon gliding. We conducted a study to assess the efficacy of VersaWrap in improving clinical outcomes related to adhesions and tethering in tendon repairs involving the hand.Materials & methodsAge, sex, injury type, mechanism of injury, visual analogue scale (VAS) pain scores, active and passive range of motion (ROM), percent return to normal function, and patient-reported outcomes forms (QuickDASH) were collected at baseline and routine follow up visits. Functional outcomes were classified according to Strickland and Glogovac grading system.Results90 patients were included, with an average age of 39.8 years and a 44% female gender. The most common mechanism of injury was sharp laceration, and the majority of repairs involved the extensor mechanism (58.8% extensor, 35.3% flexor, 5.8% both). At a mean follow-up of 4.6 months, the mean active and passive ROM was 88.8% and 94.3%, respectively. Mean percent return of function was 87.7%. Good or Excellent functional outcomes were achieved in 92.3% of patients – 70.5% Excellent, 21.8% Good, 6.4% Fair, 1.3% Poor. The average QuickDASH score was 30.7, and the average final VAS pain score was 1.3.ConclusionsTendon repairs and tenolysis procedures often result in reduced functionality due to impeded tendon gliding, and there is currently no consensus on optimal treatment to prevent tethering to surrounding tissues. The VersaWrap Tendon Protector creates a gelatinous layer between the tendon and surrounding soft tissue to improve gliding resistance, thereby limiting tendon sheath adhesions. Our data suggests that VersaWrap may be a useful adjunct in preventing tendon tethering adhesion post-repair.